Renewable Energy (Solar and Wind) Generation and its Effect on some Variables for Selected EU Countries with Panel VAR Model - Alam, Shahi Md. Tanvir (International Journal of Energy Economics and Policy, 2022)
Keeping the world livable, the policy makers are giving their extended focus on green energy. They are trying to move on hand-on-hand with rising green energy and lessening carbon dioxide (CO2) emission steading the economic activities specially for the open and developing countries. This can be helpful to provide a more lucrative economic environment to meet the extended demand of the society. The paper highlights to find out whether the economic growth, renewable energy consumption, fossil fuel-based energy generation and CO2 emission are significantly impactful on renewable energy generation or not? Is there any mutual, bi-directorial, unidirectional relationship with each other? For this, the Vector Autoregression (VAR) model is run. The paper focuses on six EU countries who are practicing auction scheme for deploying robust green energy (especially solar and wind) by reducing dependency on fossil fuel and expanding their economy with less CO2 emission. The result of the analysis shows that a positive influence of each concern variable on renewable energy (RE) generation and auction scheme might have a significant impact if robustness of the generation occurs.